2017
DOI: 10.1016/j.athoracsur.2017.05.072
|View full text |Cite
|
Sign up to set email alerts
|

Novel Debate-Style Cardiothoracic Surgery Journal Club: Results of a Pilot Curriculum

Abstract: Our novel debate-style cardiothoracic surgery journal club is an effective educational intervention for cardiothoracic surgery trainees to acquire, retain, and gain practice in applying specialty-specific literature-based evidence to controversial case-based issues. Evaluation by multi-institutional expansion is needed to validate our preliminary findings in this initial trainee cohort.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Experiences with debate-style journal clubs, for example, suggest the possibility of virtually extending traditional educational paradigms beyond single institutions and geographic regions. 18 Broadcasting journal clubs through social media has been successful in reaching larger audiences. 19 Similar opportunities arise for educational groups, such as the Thoracic Education Cooperative Group, to expand their networks into the virtual world.…”
Section: The Possibilitiesmentioning
confidence: 99%
“…Experiences with debate-style journal clubs, for example, suggest the possibility of virtually extending traditional educational paradigms beyond single institutions and geographic regions. 18 Broadcasting journal clubs through social media has been successful in reaching larger audiences. 19 Similar opportunities arise for educational groups, such as the Thoracic Education Cooperative Group, to expand their networks into the virtual world.…”
Section: The Possibilitiesmentioning
confidence: 99%
“…published in cardiothoracic surgery to engage manuscript authors, readers, and the virtual community in scholarly discussion. [2][3][4][5][6][7][8] Article-level metrics (Altmetrics) are emerging as an important measure of academic impact 9 and are intended to bring a complementary online dimension to traditional citation-based metrics, with real-time data addressing how articles are being shared and discussed globally. Importantly, previous investigations have demonstrated that high online social media attention has been correlated with subsequent article access and citations.…”
mentioning
confidence: 99%
“…Virtual classrooms. Teleconferencing of grand rounds; educational and case conferences; morbidity and mortality rounds; debate-style journal clubs, as implemented by the University of Texas MD Anderson Cancer Center 16 ; and faculty-led and -scored mock orals, such as those at the University of Wisconsin 17 allow academic instruction to continue. The role of virtual technical-skills training through livestream, augmented and virtual reality, wearable and head-mounted devices, and pocket vessel-anastomosis kits could be expanded to incorporate new dimensions, audio and tactile feedback, and hands-on remote simulations.…”
Section: Contemporize Cardiothoracic Surgical Educationmentioning
confidence: 99%